'A Volcanic Incident': Towards a Geopolitical Aesthetics of the Subterranean. Issue 1 (1st January 2020) - Hawkins, Harriet
ABSTRACT: This article experiments with the basis for a geopolitical aesthetics of the subterranean. It does so using a particular 'Volcanic Incident' – the brief emergence of Ferdinandea island in the Mediterranean in 1831 – and a range of visual and textual inscriptions around this geophysical event – from the art work Emergent Landmass (A Chronicle of Disappearance) [2006] by artist Ilana Halperin to military dispatches. Bringing together these various sources the article considers firstly how the subterranean might 'unground' geopolitical ideas and practices, and secondly how we come to know, or to sense subterranean volumes, an important aspect of controlling them. Evolving propositions around a geopolitical subterranean aesthetics, the article explores concerns with a subterranean optics, with the sensing of dynamic earth systems, and with issues around scale with respect to concerns with the geologic . From within the context of this specific case study, the article reflects on how it is that subterranean aesthetics might have wider purchase on the relations between terrains and territory, the vertical and the volumetric, and the geopolitical, geophysical and geopower.